2007
DOI: 10.1002/adsc.200600600
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dimeric and Tetrameric μ‐Hydroxide Ytterbium(III) Binaphtholate Complexes

Abstract: This manuscript is dedicated to Prof. M. Shibasaki, whose creativity and insight has changed the way we think of asymmetric Lewis acid catalysis.Supporting information for this article is available on the WWW under http://asc.wiley-vch.de/home/.Abstract: Shibasakis heterobimetallic Lewis acids,Ln (M = Li, Na, K and Ln = lanthanide), are an exceptionally useful class of asymmetric catalysts that exhibit high levels of enantioselectivity across a wide range of reactions. In many instances, it is necessary to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The 1 H and 13 C{ 1 H} NMR spectra of ( S )-1-La , ( S )-1-Pr , and ( S )-1-Eu were recorded in THF- d 8 and were similar to reported spectra for the [Li 3 (THF) n ][(BINOLate) 3 RE(THF)] (RE = La ( ( S )-2-La ), Pr ( ( S )-2-Pr ), Eu ( ( S )-2-Eu )) complexes. ,, As expected, ( S )-1-La is diamagnetic, with resonances ranging from 7.78 to −1.01 ppm, while ( S )-1-Eu and ( S )-1-Pr exhibit paramagnetically shifted and broadened resonances ranging from 18.78 to −7.98 ppm and 13.86 to −6.33 ppm, respectively (spectra are provided as Supporting Information). The resonances for the zinc-bound ethyl groups of ( S )-1-RE are diastereotopic due to the chiral environment of the BINOLate ligands.…”
Section: Results and Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The 1 H and 13 C{ 1 H} NMR spectra of ( S )-1-La , ( S )-1-Pr , and ( S )-1-Eu were recorded in THF- d 8 and were similar to reported spectra for the [Li 3 (THF) n ][(BINOLate) 3 RE(THF)] (RE = La ( ( S )-2-La ), Pr ( ( S )-2-Pr ), Eu ( ( S )-2-Eu )) complexes. ,, As expected, ( S )-1-La is diamagnetic, with resonances ranging from 7.78 to −1.01 ppm, while ( S )-1-Eu and ( S )-1-Pr exhibit paramagnetically shifted and broadened resonances ranging from 18.78 to −7.98 ppm and 13.86 to −6.33 ppm, respectively (spectra are provided as Supporting Information). The resonances for the zinc-bound ethyl groups of ( S )-1-RE are diastereotopic due to the chiral environment of the BINOLate ligands.…”
Section: Results and Discussionsupporting
confidence: 74%
“…We have recently shown that the primary determinants in the ability of Shibasaki’s complexes [M 3 (THF) n ][(BINOLate) 3 RE] to bind substrate analogues and/or Lewis basic ligands at the lanthanide cation are dependent on the size of the main group metal cation and its ability to form π-arene type noncovalent interactions with the BINOLate ligands . When the main-group metal is lithium, binding of substrate analogues to the rare-earth cation occurs readily and can be observed both in the solid state by X-ray crystallography and in solution by NMR spectroscopy.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 On standing, solutions of K 3 (THF) 6 (BINOLate) 3 Yb formed Xray quality needles. Surprisingly, an unprecedented helical polymer, [K 3 (THF) 2 (BINOLate) 3 Yb] n , was observed ( Figure 5).…”
mentioning
confidence: 99%
“…We found that the commercially available, inexpensive RE­(NO 3 ) 3 ·(H 2 O) x salts could be used in the synthesis of RETMGHB up to a 25 g scale in combination with 3 equiv of ( S )-BINOL and 6 equiv of tetramethyl guanidine (TMG, Figure ). Remarkably, tetramethyl guanidinium cation-containing (TMGH + ) complexes [(TMGH) 3 ]­[RE III (( S )-BINOLate) 3 ] (RETMGHB) withstand hydrolysis, which we attribute to the strong directionality of H-bonding between TMGH + and BINOLate oxygens. This limits structural reorganization needed for water coordination, a key requirement for hydrolysis.…”
Section: Understanding and Expansion Of The Catalysis Of Shibasaki’s ...mentioning
confidence: 98%